Is doctors' self interest undermining the National Health Service. Issue 7587 (1st February 2007) - Maynard, Alan
Abstract : Recent newspaper headlines have suggested that doctors' pay is responsible for the financial crisis in the NHS. Alan Maynard argues that financial and other self interest is endangering the service, but Laurence Buckman believes the renumeration is justified